A novel mouse model that develops spontaneous arthritis and is predisposed towards atherosclerosis. Issue 1 (26th June 2012) - Rose, Shawn; Eren, Mesut; Murphy, Sheila; Zhang, Heng; Thaxton, Colby Shad; Chowaniec, Jaime; Waters, Emily A; Meade, Thomas J; Vaughan, Douglas E; Perlman, Harris
Abstract : Objectives: Patients with rheumatoid arthritis (RA) have a reduced life expectancy due to increased cardiovascular disease. The lack of a suitable animal model resembling both RA and atherosclerosis has hindered studies demonstrating a direct link between systemic inflammation in RA and the development of atherosclerosis. Our objective was to overcome this barrier by generating an animal model (K/BxA g7 ) that spontaneously develops both RA-like disease and atherosclerosis. Methods: Arthritis severity was evaluated using clinical indices and immunohistochemical staining of ankle joint specimens. Aortic atherosclerosis was delineated via Sudan IV staining and immunohistochemical analysis. Serum cholesterol and lipoprotein levels were measured using enzymatic assays. Serum levels of cytokines, chemokines and adipokines were determined by Luminex assays. Results: K/BxA g7 mice developed a destructive arthropathy followed by prominent aortic atherosclerosis. These animals also displayed dyslipidaemia, characterised by reduced serum levels of total cholesterol and high-density lipoprotein, and increased low-density lipoprotein (LDL)/vLDL compared with control mice. Further, there were higher levels of circulating inflammatory mediators, such as interleukin-6, sRANKL and CCL5 in atherosclerotic K/BxA g7 mice compared with controls. Treatment with etanercept reduced arthritis and atherosclerosis development in K/BxA g7 mice. Conclusions: K/BxA g7 mice recapitulate the same sequence of events occurring in patients with RA, namely an erosive, inflammatory arthritis followed by atherosclerosis. These data suggest that the K/BxA g7 mouse is a novel system for investigating the interplay between systemic inflammation occurring in RA and the development of atherosclerosis.